Pauline theology and the problem of death - Longarino, Joseph 1987-; Duke University; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2021)
Cover -- Title -- Acknowledgments -- Table of Contents -- Abbreviations -- Introduction -- Chapter 1: The Problem of Mortality in Paul and Pauline Scholarship -- 1.1 Pauline Studies at the Turn of the Twentieth Century -- 1.1.1 The Ethical-Subjective Interpretation -- 1.1.2 The Physicalist-Objective Interpretation -- 1.1.2.1 Hermann Lüdemann -- 1.1.2.2 Richard Kabisch -- 1.1.2.3 William Wrede -- 1.1.2.4 Albert Schweitzer -- 1.1.3 Evaluation of the Physicalist Position -- 1.2 The Reaction to the Physicalist Interpretation -- 1.2.1 Rudolf Bultmann's Non-cosmic View -- 1.2.2 Evaluation of Bultmann -- 1.3 Reactions to Bultmann: Cullmann and Käsemann on the Centrality of the Cosmic Future Redemption -- 1.3.1 Oscar Cullmann -- 1.3.2 Evaluation of Cullmann -- 1.3.3 Ernst Käsemann -- 1.3.4 Evaluation of Käsemann -- 1.4 Sensing an Inconsistency in Pauline Studies: J. Christiaan Beker and Martinus C. de Boer on Loose Ends -- 1.4.1 J. Christiaan Beker -- 1.4.2 Evaluation of Beker -- 1.4.3 Martinus C. de Boer -- 1.4.4 Evaluation of de Boer -- 1.5 Pauline Studies Since Beker and de Boer: Overlooking the Problem -- Chapter 2: The Problem of Sin and Death -- 2.1 Introduction -- 2.2 The Problem of Sin in Romans 5-8 -- 2.2.1 The Cosmic View of Sin -- 2.2.1.1 Sin as a Universally Determinative Reality -- 2.2.1.2 Sin as a Force Exceeding and Prior to Human Action -- 2.2.1.3 Finding a Context: Apocalyptic Superhuman Powers? -- 2.2.1.4 Summary and Evaluation of the Cosmic View -- 2.2.2 Sin as the Passions -- 2.2.2.1 The Scope of the Problem of the Passions: Limited or Universal? -- 2.2.2.2 The Case for Understanding Sin as the Passions -- 2.2.2.3 Summary of Sin in Romans 5-8 -- 2.3 The Ongoing Indwelling of Sin in the Christian -- 2.3.1 Deliverance from Sin -- 2.3.1.1 Romans 6:1-11 -- 2.3.1.2 Romans 6:12-23 -- 2.3.1.3 Romans 8:1-13 -- 2.3.1.4 Romans 5:12-21.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Hochschulschrift